2020
DOI: 10.1021/acs.orglett.0c00053
|View full text |Cite
|
Sign up to set email alerts
|

Modular Synthesis of Polycyclic Alkaloid Scaffolds via an Enantioselective Dearomative Cascade

Abstract: The polycyclic core of the akuammiline alkaloids can be synthesized from simple tryptamine and tryptophol derivatives via a Ag(I)-catalyzed enantioselective dearomative cyclization cascade sequence. The complex tetracyclic scaffolds are prepared via a rapid, versatile, three-step modular synthesis from simple commercially available indole derivatives in high yields and enantiomeric excess (up to 99% yield and >99% ee).C omplex polycyclic scaffolds are widely present in biologically important alkaloid natural p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 72 publications
1
13
0
Order By: Relevance
“…In all cases the calculated transition states for carbon–carbon bond formation are located at low energy (<41 kJ mol –1 with respect to the reference state) and the C–C bond formation ( 1 → 2 ) step was calculated to be almost barrierless. These results, and others, demonstrate the synthetic versatility of 1 as a framework to access a range of important structural motifs.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…In all cases the calculated transition states for carbon–carbon bond formation are located at low energy (<41 kJ mol –1 with respect to the reference state) and the C–C bond formation ( 1 → 2 ) step was calculated to be almost barrierless. These results, and others, demonstrate the synthetic versatility of 1 as a framework to access a range of important structural motifs.…”
Section: Introductionsupporting
confidence: 65%
“… 5 , 35 Avoiding bis indolemethane formation is therefore a significant challenge, but one we were confident could be overcome by harnessing the unique reactivity of ynones. 3 , 5 , 8 , 9 , 11 , 13 In our previous work, we have shown that the electron-withdrawing carbonyl group of the ynone moiety can significantly enhance the reactivity of the alkyne when treated with a Au(I) catalyst. This enables ynones to be coupled with indoles under very mild conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This manuscript concerns a three-step cascade reaction sequence, starting from indole-tethered ynones 1 (Scheme ). In recent years, ynones of this type have emerged as valuable precursors for the preparation of a diverse array of molecular scaffolds. For example, our groups and others have shown that the activation of the alkyne moiety of 1 promotes efficient dearomatizing spirocyclization , to form medicinally important spirocyclic indolenines 2 ; , this is most commonly done using π-acidic catalysts (especially Ag­(I) species), although Brønsted acids, palladium­(II) complexes, and electrophilic halogenation reagents can also be used ( 1 → 2 , Scheme a, step 1). ,, Our groups have also shown that dearomatization works well on 2-halogenated indoles (i.e., 1 where X = Cl, Br or I) and that the resulting indoleninyl halide products (i.e., 2 where X = Cl, Br or I) can be transformed further via reaction with nucleophiles, or via Pd-catalyzed cross-coupling, to substitute the halide for various other groups ( 2 → 3 , Scheme a, step 2) . Finally, our groups and others have demonstrated that spirocyclic indolenines of the form 3 will rearrange via a one-atom ring expansion reaction to form annulated quinolines, with both acidic and basic reagents able to promote this transformation ( 3 → 4 , Scheme a, step 3) …”
mentioning
confidence: 99%
“…Quinolines are found in many marketed drugs, as well as in various other applications . On the basis of a growing understanding of each of the three individual processes discussed above, ,, we recognized that certain reagents may be able to promote all three steps and enable the transformation of 1 into 4 via a single-cascade process (Scheme b); such a reagent would need to act as an acid to promote step 1, a nucleophile in step 2, and a Brønsted acid to promote step 3. The successful realization of this strategy is reported herein, with thiols emerging as the optimum “multitasking” reagent class capable of promoting the envisaged cascade, under remarkably mild and operationally simple conditions.…”
mentioning
confidence: 99%
“…A similar type of activation of alkynes using Ag(I) for the construction of the tetracyclic hydrocarbazole skeleton was reported by Unsworth and co-workers (Scheme 5). 26,27 The 6-endo-dig cyclization of ynone 32 proceeded under similar conditions to those reported by Wang, and various tetracyclic hydrocarbazoles 35 were obtained in high yield with high enantioselectivity. The enantioselectivity of the products increased as the bulkiness of the R group was increased (35a-35c).…”
Section: Intramolecular Alkylationmentioning
confidence: 72%